The Influence of Organizational Commitment and Competence on Employee Performance with Work Performance as an Intervening Variable at the Population and Civil Registration Service of Pesisir Selatan Regency - Ananta, Cantika; Marta Widian Sari, Marta; Silvia Sari, Silvia (Social Science Studies, 2025)
Research Aims: The aim of this research is to examine the influence of organizational commitment and competence on employee performance with work performance as an intervening variable. This research specifically targets employees at the Pesisir Selatan Population and Civil Registration Service. Design/methodology/approach: This research uses a quantitative approach with the Partial Least Squares structural equation model (PLS-SEM) to predict and confirm the given hypothesis. This research uses a questionnaire to collect data on employees of the Department of Population and Civil Registry of the Pesisir Selatan. Respondents in this study totaled 40 respondents Research Findings: From the discussion in the previous chapters, it can be concluded that organizational commitment and competence have a positive and significant effect on work performance at the Pesisir Selatan Regency Population and Civil Registration Service, and competence also has a positive and significant effect on employee performance. Even though organizational commitment has a negative and insignificant direct influence on employee performance, through work performance as an intervening variable, organizational commitment has a positive and significant influence on employee performance. Apart from that, work performance has been proven to have a positive and significant effect on employee performance in this agency. Theoretical Contribution/Originality: This research contributes to the theoretical understanding that organizational commitment does not have an influence on employee performance, but competence has a positive influence on employee performance. Apart from that, there is also an indirect influence, namely work performance as an intervening variable which has an indirect influence from organizational commitment and competency on employee performance at the Pesisir Selatan population and Civil Registration Service. Keywords: Organizational Commitment; Competence; Employee Performance, Work performance